Differing roles of lifelong learning: Hedging against unemployment risks from skill obsolescence or boosting upward career mobility? - Schultheiss, Tobias [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2021)
„This paper examines the role of lifelong learning in counteracting skill depreciation and obsolescence. We build on findings showing that different skill types have structurally different depreciation rates. We differentiate between hard and soft skills and measure the relative importance of these two skill types at the occupational level. As data source we draw on a large sample of job advertisements and a categorization of their skill requirements through a machine-learning algorithm. We analyze lifelong learning effects for “harder” occupations (with relatively more hard than soft skills) versus “softer” occupations,. Our results reveal important patterns of skill depreciation and counteracting lifelong learning effects: In harder occupations, the role of lifelong learning is primarily as a hedge against unemployment risks caused by fast-depreciating hard skills; in softer occupations, this role instead lies mostly in acting as a boost to wage gains and upward career mobility as workers build on a value-stable skill foundation.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; G 2.3.4 Qualifikationswandel; G 1.3.3.1 Qualifikationsverwertung; 370; Lebenslanges Lernen; Bildungsertrag; Beschäftigungsfähigkeit; Qualifikationsverwertung; Dequalifizierung; Arbeitsmarktrisiko; Weiterbildung; Schweiz